Forensic Accounting And Whistleblowing In Fraud: A Literature Study - Wulan Safitri; Iman Karyadi; Dijah Julindrastuti (Doctoral Program of Social Science Pasundan University, 2026)
This study analyzes the role of forensic accounting and whistleblowing in uncovering fraud amidst high corruption challenges. Using a literature review approach, data was collected from 50 research articles. The results indicate that forensic accounting is effective in detecting and uncovering fraud through in-depth analysis, while whistleblowing serves as a crucial reporting mechanism for prevention and mitigation. The combination of these two approaches creates more comprehensive oversight, particularly in the public and banking sectors, in preventing fraud. This study also recommends further study to explore the influence of new technologies in forensic accounting.